2009
DOI: 10.1080/14764170902842531
|View full text |Cite
|
Sign up to set email alerts
|

The use of low-level light for hair growth: Part I

Abstract: LLLT may be a promising treatment option for patients who do not respond to either finasteride or minoxidil, and who do not want to undergo hair transplantation. This technology appears to work better for some people than for others. Factors predicting who will most benefit are yet to be determined. Larger, longer-term placebo-controlled studies are needed to confirm these findings, and demonstrate statistical significance, or refute them altogether.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 17 publications
4
65
1
Order By: Relevance
“…In a clinical study, seven patients with a diagnosis of AGA were exposed to LLLT twice weekly for 20 min for 3-6 months. An increase in the number of terminal hair, a decrease in the number of vellus hair, and an increase in shaft diameter were observed in this study but these changes were not statistically significant [89].…”
Section: Androgenetic Alopeciamentioning
confidence: 66%
See 2 more Smart Citations
“…In a clinical study, seven patients with a diagnosis of AGA were exposed to LLLT twice weekly for 20 min for 3-6 months. An increase in the number of terminal hair, a decrease in the number of vellus hair, and an increase in shaft diameter were observed in this study but these changes were not statistically significant [89].…”
Section: Androgenetic Alopeciamentioning
confidence: 66%
“…It is not exactly known, how these light sources can induce hair growth. One possible mechanism is the activation of silent hair follicles or the synchronization of hair growth cycles by direct light stimulation [89]. Radmanesh et al identified different mechanisms for developing hypertrichosis after the IPL.…”
Section: Androgenetic Alopeciamentioning
confidence: 99%
See 1 more Smart Citation
“…Sevaral clinical reports [1][2][3] have suggested that hair growth is promoted by low-level laser therapy (LLLT), defined as therapy using red-beam or near-infrared laser with a wavelength of 600-1100 nm and an output power of 1-500 mW, since Mester et al [4] reported effect of LLLT on hair growth in 1967. However, the irradiation area of laser system is small, and most systems are expensive and relatively immobile.…”
Section: Narrow-band Red Led Light Promotes Mouse Hair Growth Throughmentioning
confidence: 99%
“…Avram MR, et al [115] performed a study in 7 patients to investigate the efficacy of LLLT in hair regrowth and found a not statistical significance decrease in the number of vellus hairs, an increase in the number of terminal hairs, and an increase in shaft diameter. No improvement in hair density was noted.…”
Section: Low-level Laser Therapymentioning
confidence: 99%